1993
DOI: 10.2307/3431378
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Increasing Incidence of Abnormalities of the Human Testis: A Review

Abstract: Recent reports have suggested that the incidence of genitourinary abnormalities in human males has increased during the past 50 years, including congenital abnormalities such as cryptorchidism and hypospadia, which seem to be occurring more commonly. Also, the incidence of testicular cancer has increased 3-to 4-fold since the 1940s. This increase seems to be worldwide including countries with a very high frequency of testicular neoplasia as well as those in which this cancer is rather uncommon. It has also bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
2
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 31 publications
(36 reference statements)
0
40
2
1
Order By: Relevance
“…For example, some studies observed that tight-fitting underwear had an adverse effect on various semen parameters1819, whereas other studies reported no adverse effect of tight-fitting underwear on semen quality 20 21. The present study did not observe that wearing tight-fitting underwear was significantly associated with semen quality but did find that wearing fibre underwear often lowered the percentage of normal sperm morphology (p=0.001) in men living in Chongqing after adjusting for confounders.…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…For example, some studies observed that tight-fitting underwear had an adverse effect on various semen parameters1819, whereas other studies reported no adverse effect of tight-fitting underwear on semen quality 20 21. The present study did not observe that wearing tight-fitting underwear was significantly associated with semen quality but did find that wearing fibre underwear often lowered the percentage of normal sperm morphology (p=0.001) in men living in Chongqing after adjusting for confounders.…”
Section: Discussioncontrasting
confidence: 78%
“…Similarly, the present study did not establish any relationship between regular exercise and semen parameters in men living in the Chongqing area. The impact of a sedentary lifestyle and having saunas on semen quality has attracted interest from researchers but the results have been inconsistent 10 1921 24–28. The present study observed no significant association between a sedentary lifestyle or taking saunas and semen quality.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…Giwercman et al (1993) in their reports have suggested that the incidence of genitourinary abnormalities in human males has increased during the past 50 years, including congenital abnormalities such as cryptorchidism and hypospadias, which seem to be occurring more commonly. The increase in these abnormalities over a relatively short period of time may be due to the environmental rather than genetic factors.…”
Section: Introductionmentioning
confidence: 94%
“…From the reproductive point of view, an increased impact on the human male gonad is of concern. [1] About 90% of undescended testes are associated with an occult inguinal hernia, especially those with minimal descent and those associated with epididymal abnormalities. Ectopic testes are associated with an inguinal hernia in about 50% of cases.…”
Section: Introductionmentioning
confidence: 99%